Measurements of droplet size in shear-driven atomization using ultra-small angle x-ray scattering. (June 2017) - Kastengren, A.; Ilavsky, J.; Viera, Juan Pablo; Payri, Raul; Duke, D.J.; Swantek, A.; Tilocco, F. Zak; Sovis, N.; Powell, C.F.
Highlights: X-ray diagnostics have for the first time been used to probe optically dense shear driven atomization. Dropet size measurements indicate a dearth of submicron droplets. This is in conflict with a popular droplet breakup model for diesel sprays. Quantitative measurements of the trends in droplet size with injection pressure, ambient pressure, and nozzle diameter in the near-nozzle region have been outlined. Abstract: Measurements of droplet size in optically-thick, non-evaporating, shear-driven sprays have been made using ultra-small angle x-ray scattering (USAXS). The sprays are produced by orifice-type nozzles coupled to diesel injectors, with measurements conducted from 1 – 24 mm from the orifice, spanning from the optically-dense near-nozzle region to more dilute regions where optical diagnostics are feasible. The influence of nozzle diameter, liquid injection pressure, and ambient density were examined. The USAXS measurements reveal few if any nanoscale droplets, in conflict with a popular computational model of diesel spray breakup. The average droplet diameter rapidly decreases with downstream distance from the nozzle until a plateau value is reached, after which only small changes are seen in droplet diameter. This plateau droplet size is consistent with the droplets being small enough to be stable with respect to further breakup. Liquid injection pressure and nozzle diameter have the biggest impact on droplet size, while ambient density has a smaller effect.